If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 2x = 7x + -27 Reorder the terms: 8 + 2x = -27 + 7x Solving 8 + 2x = -27 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 8 + 2x + -7x = -27 + 7x + -7x Combine like terms: 2x + -7x = -5x 8 + -5x = -27 + 7x + -7x Combine like terms: 7x + -7x = 0 8 + -5x = -27 + 0 8 + -5x = -27 Add '-8' to each side of the equation. 8 + -8 + -5x = -27 + -8 Combine like terms: 8 + -8 = 0 0 + -5x = -27 + -8 -5x = -27 + -8 Combine like terms: -27 + -8 = -35 -5x = -35 Divide each side by '-5'. x = 7 Simplifying x = 7
| -3+x=3x-25 | | 10x-6=66 | | 13q-3q= | | -4x+1=2x-11 | | (x+15)/2=13 | | 6-6x=-5x+0 | | (x^2-6x-16)/(x^2-36) | | -2+3x=2x+9 | | 16/3=32/x | | 45-14b+b^2=0 | | -3/y=-6 | | -12=-3(3x-2) | | 10u+19u= | | 5=-7/y | | h=-16t^2+113t+93 | | -8=-6/y | | 2w^2-5w=42 | | Y=4x-325 | | 3y+12=y+8 | | X=4x-325 | | 11x^2+55x-13000=0 | | 15b-11b=28 | | -6(x+5)=24 | | 9x*9x-49=0 | | X^2+14x+49+y^2-14y+49=49 | | 2logx=4 | | 4x=x+325 | | 5x*5x-7x+2=0 | | 8y+6y-2y=36 | | 0.5=0.2-10 | | X*x*x+4x*4x-12x=0 | | Log(2)16=4 |